Study of structural, mechanical and thermal properties of θ-Fe3C, o-Fe7C3 and h-Fe7C3 phases using molecular dynamics simulations - Ghosh P.S.; Ali K.; Vineet A.; Voleti A.; Arya A. (My University, 2025)
Structural, mechanical and thermal properties of θ-Fe3C cementite, o-Fe7C3 and h-Fe7C3, the common carbides in steels and earth's inner core, are calculated upto 450 GPa pressure and 2000 K temperature range using classical molecular dynamic (MD) simulations. A thorough evaluation of phase stability and elastic properties of several iron-carbides (γ′-FeC, η-Fe2C, ζ-Fe2C, h-Fe7C3, o-Fe7C3, χ-Fe5C2, θ-Fe3C, γ′-Fe4C, γ″-Fe4C and α′-F16C2) is performed using four MD potentials (namely, MEAM, Tersoff and EAM/FS) for broad comparison of these potentials at static condition. The MD calculated pressure-volume, pressure-elastic constants and volume-temperature relations for θ-Fe3C, o-Fe7C3 and h-Fe7C3 phases are thoroughly compared with available experimental and first principles calculated values to assess the range of applicability and deficiencies of these interatomic potentials. Our enthalpy calculations suggest that o-Fe7C3 is more stable than Eckstrom-Adcock hexagonal iron carbide (h-Fe7C3) upto 450 GPa and 2000 K (Earth's core condition) which is in agreement with recent experiment. Our MD calculated longitudinal sound velocities match well with experiments (within 2%) upto 75 GPa and starts deviating from Birch's law at high pressures due to nonlinear interaction of phonon modes. The MD calculated pressure-volume-temperature relation of θ-Fe3C phase reproduces experimental values and pressure-volume-temperature relation of o-Fe7C3 phase is predicted upto 200 GPa and 2000 K. The MD calculated melting temperatures of θ-Fe3C and Fe7C3 using two-phase simulations match well with experimental values within their errorbars at 50 GPa and higher pressures. © 2017 Elsevier B.V.